Representation of Qur'anic Stories in The Journey Anime - Anggara, Jefry; Bakti, Andi M. Faisal; Muttaqin, Mohammad Izdiyan (Asian Journal of Philosophy and Religion, 2025)
The Journey anime, inspired by Qur’anic stories, faces challenges in maintaining narrative integrity and conveying Islamic moral values. This study evaluates the representation of Qur’anic elements in the anime and its impact on viewers’ understanding of Islam and religion. Using a qualitative method and the “Questions of Representation” framework, the research applies discourse analysis supported by media studies, Islamic history, and Qur’anic studies. Primary data are taken from the anime, with secondary sources from academic literature. Findings show that while the anime preserves key Islamic messages, it offers a superficial portrayal and lacks depth in religious authenticity and gender representation. The study highlights the importance of accurate and ethical portrayals of religion in anime.